Gear Acquisition Syndrome Consumption of Instruments and Technology in Popular Music - Herbst, Jan-Peter (University of Huddersfield Press, 2021)
"Gear Acquisition Syndrome, also known as GAS, is commonly understood as the musicians' unrelenting urge to buy and own instruments and equipment as an anticipated catalyst of creative energy and bringer of happiness. For many musicians, it involves the unavoidable compulsion to spend money one does not have on gear perhaps not even needed. The urge is directed by the belief that acquiring another instrument will make one a better player. This book pioneers research into the complex phenomenon named GAS from a variety of disciplines, including popular music studies and music technology, cultural and leisure studies, consumption research, sociology, psychology and psychiatry. The newly created theoretical framework and empirical studies of online communities and offline music stores allow the study to consider musical, social and personal motives, which influence the way musicians think about and deal with equipment. As is shown, GAS encompasses a variety of practices and psychological processes. In an often life-long endeavour, upgrading the rig is accompanied by musical learning processes in popular music."